The moderating effect of leadership style on the relationship between job description and employee performance in the Omani public sector - Shahab Ahmed Salim Mubarak AL Rawas; Mohd Dan Jantan (Cogent Business & Management, 2023)
The performance of employees is important for all organizational stakeholders. Prior research concentrated on how well workers performed in private-sector businesses in developed nations, with the public sector in emerging nations receiving little attention. This study's goal is to investigate how job description (JD) influences employee performance (EP) in Omani public sector, and it is to examine the moderating role of leadership style in the relationship between JD and EP. Organizations in Oman's governmental sphere make up the study's population. However, five designated ministries are chosen to represent the public sector. Stratified random sampling is used to gather the data using a questionnaire. A total of 420 responses were collected. Data were analyzed using analysis of a moment structures (AMOS). The findings demonstrated that JD has a significant positive impact on EP. In addition, transactional leadership but not transformational leadership moderated positively the effect of JD on EP of the Omani public sector. Decision makers are advised to simplify and accurately design the job of employees and to link pay with performance.
Keywords: 650; employee performance; job description; transactional leadership; transformational leadership